Urban Farming Program For Women PKK Manang Village To Improve Family Food Security Value In The Era Of The Pandemi Transition Covid-19 - Wahyu Adhi Saputro; Musta’in Musta’in; Ahmad Fauzi (Faculty of Law, 2020)
Food is indeed one of the mandatory things that must be fulfilled. However, the current condition of thepopulation growth which continues to increase is not accompanied by an increase in agricultural land sothat the available food stock may one day be insufficient. This makes a food problem which is closelyrelated to food security. PKK mothers are people who think about food for their families so that they havea huge influence. The decline in the amount of land and reduced food stocks in the era of the Covid-19pandemic because people flocked to buy large amounts of food stocks became a problem that was raisedin this community service program. The aim of this program is to introduce urban farming methods thatcan be done in empty house areas to increase food access to increase the value of family food security. Themethod used in the community service program was the online extension method and then carried out theurban farming practice which was carried out by one of the PKK mothers in Manang Village. It is hopedthat this example can become a role model for the people around him. The results of the community serviceprogram that have been carried out have improved the skills of PKK Manang Village women in cultivatingplants in the area of their home yard that is still empty or not in use. The existence of planting crops thatcan be harvested can meet food needs so that from the dimension of accessibility to food security it can befulfilled properly.